Enhanced acetone-butanol-ethanol production from lignocellulosic hydrolysates by using starchy slurry as supplement. (November 2017) - Yang, Ming; Kuittinen, Suvi; Vepsäläinen, Jouko; Zhang, Junhua; Pappinen, Ari
Highlights: The normal supplements of ABE fermentation medium were replaced with starchy slurry. The starchy slurry as supplement ensured the essential nutrients for ABE fermentation. Supplement of the starchy slurry enhanced the ABE production from lignocelluloses. The starchy slurry was helpful for the utilization of xylose by C. acetobutylicum. Abstract: This study aims to improve acetone-butanol-ethanol production from the hydrolysates of lignocellulosic material by supplementing starchy slurry as nutrients. In the fermentations of glucose, xylose and the hydrolysates of Salix schwerinii, the normal supplements such as buffer, minerals, and vitamins solutions were replaced with the barley starchy slurry. The ABE production was increased from 0.86 to 14.7 g/L by supplementation of starchy slurry in the fermentation of xylose and the utilization of xylose increased from 29% to 81%. In the fermentations of hemicellulosic and enzymatic hydrolysates from S. schwerinii, the ABE yields were increased from 0 and 0.26 to 0.35 and 0.33 g/g sugars, respectively. The results suggested that the starchy slurry supplied the essential nutrients for ABE fermentation. The starchy slurry as supplement could improve the ABE production from both hemicellulosic and cellulosic hydrolysate of lignocelluloses, and it is particularly helpful for enhancing the utilization of xylose from hemicelluloses.